Numerical Investigation of the Effect of Geocell-Reinforced Cushion on Load Distribution and Settlement Reduction in Unconnected Piled Raft Foundations - Pourgholamali, Mojtaba; Asgharpour, Farzin (Fırat University, 2024)
The effect of geocell-reinforced cushion on load distribution and settlement reduction in unconnected piled raft foundations was investigated. Modeling and analysis of various scenarios were carried out using Abaqus software. In this research, a total of nine models, including one connected, three unconnected and unreinforced, and five unconnected and reinforced with geocell, were analyzed. Cushions with thicknesses half of, equal to, and twice that of the foundation were used. The results have shown that optimal outcomes in terms of load distribution efficiency and settlement reduction are achieved when the cushion's stiffness is set at half that of the foundation. The obtained results demonstrate the positive effect of geocell reinforcement in enhancing the performance of unconnected piled raft foundations. The introduction of geocells into the models increases soil stiffness and pile load ratio, consequently enhancing the load-bearing capacity of the piled raft foundation compared to the unreinforced models. The study's findings pave the way for a more effective use of geocells in civil engineering applications, particularly in scenarios demanding high load-bearing capacity and minimal foundation settlement.

Temassız kazıklı radye temellerde geohücre ile güçlendirilmiş yastıkların yük dağılımına ve oturmaların azaltılmasına etkisi araştırılmıştır. Abaqus yazılımı kullanılarak çeşitli durumların modellemesi ve analizi gerçekleştirilmiştir. Bu çalışmada bir temaslı, üç temassız ve takviyesiz, beş temassız ve geohücre ile güçlendirilmiş durumlar olmak üzere toplamda dokuz model incelenmiştir. Kalınlıkları temel kalınlığının yarısı, eşit ve temel kalınlığının iki katı kadar olan yastık modelleri kullanılmıştır. Sonuçlar, yük dağıtım verimliliği ve oturmanın en aza indirilmesi açısından en iyi sonuçların, yastığın rijitliği temelin rijitliğinin yarısı kadar olduğu modellerde elde edildiğini göstermiştir. Elde edilen sonuçlar, temassız kazıklı radye temellerin performansını arttırma noktasında geohücre takviyesinin olumlu etkisini göstermektedir. Geohücrenin modellere eklenmesi zeminin rijitliğini ve kazık yük oranının artmasını sağlamakta ve dolayısıyla güçlendirilmemiş modellere kıyasla kazıklı radye temelin yük taşıma kapasitesini arttırmaktadır. Çalışmanın bulguları, geohücrelerin inşaat mühendisliği uygulamalarında özellikle yüksek yük taşıma kapasitesi ve minimum temel oturmasını gerektiren durumlarda daha etkin bir şekilde kullanılması için uygun zemini hazırlamaktadır.
Temassız Kazıklı Radye Temellerde Geohücre ile Güçlendirilmiş Yastıkların Yük Dağılımı ve Oturmanın Azaltılmasına Etkisinin Nümerik Olarak İncelenmesi
Keywords: Civil Engineering (Other); İnşaat Mühendisliği (Diğer)